Histopathological Examination of Gastrectomy Specimens After Laparoscopic Sleeve Gastrectomy and the Importance of Preoperative Endoscopy - Öztütüncü, Özgür; Şanlı, Ahmet Necati; Taşkın, Halit Eren; Tozakoğlu, Batuhan; Zengin, Abdullah Kağan (Cerrahpaşa Medical Journal, 2022)
Objective: Laparoscopic sleeve gastrectomy is the most commonly performed procedure for the surgical treatment of obesity. In this study, we aimed to analyze the histopathological specimens of laparoscopic sleeve gastrectomy patients. Methods: A total of 232 patients who have undergone the laparoscopic sleeve gastrectomy procedure between the years 2015 and 2020 were included in this study. The pathology reports of these patients were evaluated from the patient files retrospectively. The age, gender, comorbid diseases, and the body mass index of each patient were noted from the patient files. None of the patients had undergone preoperative endoscopy. Results: In the study, 87 (37.5%) of the patients were male and 145 (62.5%) were female. The mean age of the patient was 42.9 ± 12.0 years and the mean body mass index was 40.2 ± 4.9. As for the comorbidities, 24.2% had diabetes mellitus, 23.3% had hypertension, and 7.8% had obstructive sleep apnea. The histopathological specimens revealed that 22 patients had intestinal metaplasia, 3 patients had gastrointestinal stromal tumor, 2 had neuroendocrine tumor, 2 had leiomyoma, 1 had squamocolumnar changes, and 1 had a hyperplastic polyp. Conclusion: Preoperative endoscopy may reveal possible benign or malignant pathologies, which will lead to better treatment of the patients. Furthermore, the post-operative histopathological analysis can reveal important pathologies that may go unnoticed in the preoperative period. Cite this article as: Öztütüncü Ö, Şanlı AŞ, Taşkın HE, Tozakoğlu B, Zengin AK. Histopathological examination of gastrectomy specimens after laparoscopic sleeve gastrectomy and the importance of preoperative endoscopy. Cerrahpaşa Med J. February 12, 2022. 46(1):26-29.